Pemberdayaan UMKM (Pemasaran dan Keuangan) Keripik Sukun di Desa Malangsari (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2021)
In economic development, the role of micro, small and medium enterprises (MSMEs) is one of the drivers of the economy. It can be proven that the existence of MSMEs is able to provide jobs, reduce the number of unemployed and become a means of introducing local products so that they can be known by all circles of society. MSMEs exist because they provide opportunities that are used by MSME actors in providing community needs, businesses that are viral and provide business opportunities, tastes, prices are affordable by the general public, there are consumers who become loyal customers, the availability of raw materials that open up business opportunities, and etc.